Text coherence in Surat (Abs): Referral as a template: التماسك النصي في سورة عبس: الإحالة أنموذجاً (المجلة العربية للعلوم و نشر الأبحاث, 2020)
This study seeks to read the Qur’anic text from the standpoint of textual linguistics, and to clarify one of the various textual interconnections in its levels, and to stand at the features of textual cohesion by referring to the pronoun in the Qur’anic text and specifically in Surat Abbas, and after the study, the effect of the pronoun in forming the interconnection between the different verses is revealed. In her objective view that was the story of the great companion who came to the Prophet, may God’s prayers and peace be upon him, and that the Qur’an is the home for purifying souls, in addition to showing the condition of a disbeliever, and finally she expressed God’s blessings on His servants whose thinking leads them to guidance and faith in the Last Day, on the Day of Resurrection Its horrors and reminded the two teams that won and lost the paradise.This study reveals harmony and cohesion between the verses, despite their different topics and the effect of the conscience in shaping the general meaning of the surah, and by this, the effectiveness of its role appears in achieving the structural cohesion of the surah, and the descriptive approach that relies on observing and extrapolating the pronoun in the verses has been followed, and the study reached several results, including the large number Referral by pronouns in the surah, where he found fifty-five pronouns in comparison to other referral tools.